THE IMPACT OF TANJUNG SAKTI AGRITOURISM ON ENVIRONMENTAL PRESERVATION IN SINDANG PANJANG VILLAGE, LAHAT REGENCY - Shomedran Shomedran; Ade Anugra Utami (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2023)
T This study aims to determine the impact of agro-tourism on environmental preservation in Sindang Panjang Village. This research uses descriptive research with a qualitative approach. Data collection used interviews, observation, and documentation methods. The subjects of this research were the manager of Agrotourism, the Sindang Panjang Village government, and the people of Sindang Panjang Village. The indicators of the research results obtained are; 1) The negative impact of agro-tourism is dependence on tourism and the seasonal nature of tourism. 2) The positive impact of Tanjung Sakti Agrotourism is to preserve, maintain, and utilize natural resources wisely. The conclusion is that Agritourism can improve people's lives and reforest nature.Keywords : Impact, Agritourism, Environmental Preservation.